Reactive Power Controller for Under-Excitation Limiter With Regard to Electromechanical Oscillations - Dusan Joksimovic; Djordje Stojic; Slavko Veinovic; Darko Marcetic (IEEE Access)
This paper presents a novel tuning algorithm for the adaptive reactive power (Var) PI controller as a control part of under-excitation limiter (UEL). The proposed algorithm is designed to adapt to changes in the synchronous generator (SG) plant dynamics without requiring prior knowledge of generator and system parameters. The algorithm is based on the reduced first-order linear plant model, whose parameters are estimated using the Recursive least-squares (RLS) algorithm. Considering that the SG is close to its stability limit when the UEL is operational, if the Var controller is not tuned well, the UEL can generate a negative damping torque on electromechanical oscillations and even lead to SG instability. The proposed algorithm solves this problem by targeting the specific frequency bandwidth of the Var control system that excludes the detected frequency of electromechanical oscillations. This mitigates the negative impact of the UEL on the damping of electromechanical oscillations and prevents overlapping of UEL action with the power system stabilizer (PSS) action. Once the plant model parameters are estimated, and the targeted control system frequency band is identified based on the measured electromechanical oscillation frequency, the controller parameters are tuned using pole-zero cancellation method. The effectiveness and performance of the proposed tuning procedure, encompassing online identification of reduced linear plant model parameters, online measurement of electromechanical oscillation frequency, and subsequent online tuning of the UEL Var controller, have been demonstrated through both simulation and experimental studies. Simulations utilized nonlinear and linear models of a 240 MVA SG connected to an infinite bus and Kundur’s two-area power system model. Experimental validation was conducted in a laboratory environment using a reduced-scale, low-power SG. Dynamic performance indices obtained from various test cases demonstrate the robustness and stability of the Var control system incorporating the UEL controller proposed in this paper.